Current management options and recent advances in IBD. Issue 22 (19th November 2014) - Warner, Ben; Irving, Peter
<x xml:space="preserve">Abstract</x> The advent of biological therapies has revolutionised the management of inflammatory bowel disease, and the imminent introduction of anti‐adhesion molecule therapy seems likely to have a big impact. Our Drug review outlines the current treatment options and examines some recent advances in diagnosis and management, followed sources of further information and an analysis of the prescription data.